Lack of proprioceptive strategy modulation leads to at-risk biomechanics for anterior cruciate ligament in healthy athletes - Picot, B.; Lempereur, M.; Morel, B.; Forestier, N.; Rémy-Néris, O. (Medicine & Science in Sports & Exercise, 2024)
Introduction Anterior cruciate ligament (ACL) injuries are frequent in handball and altered sensory integration may contribute to increased injury risk. Recent evidence showed that proprioceptive postural control strategies differ among athletes. The aim of this study was to evaluate the relationship between proprioceptive strategy and biomechanics during side-cutting manoeuvres.